2010
DOI: 10.1111/j.1365-2400.2009.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating angling effort and participation in a multi‐user, inland fishery in South Africa

Abstract: Angler counts, on-lake interviews and a household survey were used to estimate angler effort and participation in Lake Gariep, South AfricaÕs largest inland water body. Annual fishing effort was estimated from instantaneous counts at 16392 angler day )1 yr )1 . Recreational and subsistence anglers contributed 41 and 59% to the total annual fishing effort, respectively. Household surveys in lakeshore settlements estimated that ‡914 anglers fished the lake and minimum daily fishing effort in one of the fishing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…This is supported by tournament data for the Free State Province, where C. carpio contributed 81% of the total weight and 77% of the total numbers of all fish landed (Table 4). The findings from tournament data were surprisingly consistent with the results of a comprehensive creel survey comprising more than 700 anglers' interviews and catch inspections at Gariep Dam, and which found that angler catches comprised mainly of C. carpio (74%), followed by L. capensis (13%) and L. aeneus (8%) (Ellender et al, 2009;2010a;2010b).…”
supporting
confidence: 76%
See 4 more Smart Citations
“…This is supported by tournament data for the Free State Province, where C. carpio contributed 81% of the total weight and 77% of the total numbers of all fish landed (Table 4). The findings from tournament data were surprisingly consistent with the results of a comprehensive creel survey comprising more than 700 anglers' interviews and catch inspections at Gariep Dam, and which found that angler catches comprised mainly of C. carpio (74%), followed by L. capensis (13%) and L. aeneus (8%) (Ellender et al, 2009;2010a;2010b).…”
supporting
confidence: 76%
“…This is anomalous in the African context as fisheries in other countries are generally heavily exploited by small-scale fishers using gears such as gill nets, seine nets and traps (Weyl et al, 2010;Cooke et al, 2013;Weyl and Cowley, 2015). Although inland fisheries in South Africa are generally considered underexploited from a harvest perspective (Weyl et al, 2007;Britz et al, 2015), case studies of angling on the Hartbeespoort Dam (Cochrane, 1987) and the Gariep Dam (Ellender et al, 2009(Ellender et al, , 2010a(Ellender et al, , 2010b suggest that harvests by recreational and subsistence anglers can be considerable. Cochrane (1987), for example, estimated a mean annual harvest of 695 tons of fish from the 2 000 ha eutrophic Hartbeespoort Dam by recreational anglers from the metropolitan settlements in Gauteng.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations